OTENTISITAS KONSEP TUHAN DALAM ISLAM - Prayogi, Arditya; Nasrullah, Riki (Yayasan Zia Salsabila, 2024)
The existence of God is also fundamental in human life because acceptance or rejection of God's entity will also have fundamental consequences. In this way, a concept of circumstances is built that seeks to improve human relations with God. This concept became known as religion. In its development, religion is part of the journey of human life as an entity that believes in God as the highest point in its life. In its development, religion emerged in an evolutionary way along with humans' ability to understand the natural surroundings which are part of their lives. This article then aims to provide an overview of the concept of authentic God that exists in Islamic beliefs. This article was prepared using a descriptive qualitative method supported by data collection methods in the form of literature studies. The concept of God in Islam negates various concepts of God in other religious and cultural traditions and civilizations which tend to be problematic and speculative. Muslims throughout the world then agreed to call the name of their God as Allah, which in the process became known to Muslims through a dogmatic-spiritual and academic-rational approach.